Criminological problems of domestic violence against women (Journal of actual problems of jurisprudence, 2021)
Domestic violence against women is a global problem that has no cultural or geographic boundaries. Violence against women in all its forms and manifestations is a violation of human rights and freedoms. The urgency of the problem of domestic violence lies in the fact that domestic violence is one of the most widespread forms of violence in women’s lives – much more widespread than physical assault or rape by strangers or acquaintances. The purpose of the article is a multifaceted analysis of the preconditions and factors of committing domestic violence for the effective prevention and fight against violence against women. The study is based on world experience and theoretical studies of scientists and international organizations, using modern criminological methodology. The article examines the factors influencing the commission of unlawful acts against women, the victimological aspect and the criminological characteristics of domestic violence. As a result of the study, conclusions are drawn, proposals for the suppression and prevention of domestic violence are presented, an analysis of the current legislation governing legal relations in the studied area is carried out, actors of the prevention of domestic violence in Kazakhstan are given.Keywords: law, domestic violence, criminological characteristics, victimology, crimes and wrongful acts against women.